1987
DOI: 10.1002/1097-0142(19870515)59:10<1810::aid-cncr2820591021>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Histologic features relating to prognosis in synovial sarcoma

Abstract: Although the American Joint Commission has classified all synovial sarcomas as "high grade," histologic subtypes can be identified. By histologically subclassifying synovial sarcoma tumors according to percent glandularity and mitotic rates, the authors were able to define high-risk and low-risk patients. Charts and original pathologic slides were reviewed on 45 synovial sarcoma patients. With a 41-month median follow-up, the low-risk patients showed 100% survival, whereas the high-risk patients showed 37% sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
3
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(44 citation statements)
references
References 7 publications
5
35
3
1
Order By: Relevance
“…Saito et al (12) showed that SYT-SSX1 and SYT-SSX2 interfere with repression of E-cadherin by Snail and Slug. The SYT-SSX1 fusion product has been proposed as a diagnostic and prognostic marker for synovial sarcoma (28,29). Cagle et al (29) have pointed out a much more favorable prognosis of biphasic "highly glandular" synovial sarcomas where greater than 50% of the tumor surface area has glandular differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saito et al (12) showed that SYT-SSX1 and SYT-SSX2 interfere with repression of E-cadherin by Snail and Slug. The SYT-SSX1 fusion product has been proposed as a diagnostic and prognostic marker for synovial sarcoma (28,29). Cagle et al (29) have pointed out a much more favorable prognosis of biphasic "highly glandular" synovial sarcomas where greater than 50% of the tumor surface area has glandular differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The SYT-SSX1 fusion product has been proposed as a diagnostic and prognostic marker for synovial sarcoma (28,29). Cagle et al (29) have pointed out a much more favorable prognosis of biphasic "highly glandular" synovial sarcomas where greater than 50% of the tumor surface area has glandular differentiation. Thus, the previous observation in synovial sarcomas by others and our current observation in leiomyosarcoma are consistent in the notion that MErT represents a beneficial clinical prognosis in mesenchymal tumors, although future studies in other sarcoma types will be needed to determine whether this is indeed the case.…”
Section: Discussionmentioning
confidence: 99%
“…et al 1989, Oda et al 1993a, b, Mullen and Zagars 1994, Singer et al 1996. Numerous patient, treatment, and tumor factors have been found to influence disease outcome (Varela-Duran and Enzinger 1982, Cagle et al 1987, Rooser et al 1989, ElNaggar et al 1990, Golouth et al 1990, Schmidt et al 1991, Brodsky et al 1992, Ladenstein et al 1993, Oda et al 1993a, b, de Leeuw et al 1994, Pappo et al 1994, Yokoyama et al 1995, Singer et al 1996, Folpe et al 1998, Kawai et al 1998, Lopes et al 1998, Bergh et al 1999, van de Rijn et al 1999). However, a comparison of these studies is hampered by their heterogeneous nature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, recent studies of synovial sarcoma have indicated that it is not a homogeneous tumor in terms of disease course and outcome (Choong et al 1995, Bergh et al 1999, Skytting et al 1999. Certain patient factors, clinical features, treatment, morphologic, flow cytometric, and cytogenetic characteristics have been found to be prognostically significant in synovial sarcoma (Wright et al 1982, Cagle et al 1987, Rooser et al 1989, El-Naggar et al 1990, Golouth et al 1990, Schmidt et al 1991, Brodsky et al 1992, Ladenstein et al 1993, Oda et al 1993a, b, Pappo et al 1994, de Leeuw et ai. 1994a, Yokoyama et al 1995, Singer et al 1996, Folpe et al 1998, Kawai et al 1998, Lopes et al 1998, Bergh et al 1999.…”
mentioning
confidence: 99%
“…1977), mitotic rate (Singer et al 1996), percent glandularity (Cagle et al 1987) and tumor necrosis (Oda et al 1993). The biphasic subtype is thought by some to have a better prognosis than the monophasic type.…”
Section: Histopathological Analysismentioning
confidence: 99%